A rare case of gastrointestinal stromal tumor presenting with closed perforation of the small intestine - Ahat ANDİCAN; Fahri GÖKÇAL; Afag AGAYEVA; Fatih GÜLŞEN; Ferhat ÖZDEN; Volkan ÖZBEN (Turkish Journal of Gastroenterology, 2019)
-